ECONOMIC ANALYSIS IN BELL PEPPER CROP ON OPEN FIELD PRODUCTION SYSTEM AND UNDER IRRIGATION DEPTHS - Rodríguez Padrón, Richard Alberto; Swarowsky, Alexandre; Schons, Alfredo; Cánepa, Pancracio; Gamazo, Pablo (Acta Iguazu, 2000)
In agriculture, the search for higher net profit is the main challenge in the economy of the producer. This study aims at the economic analysis in the bell pepper crop on open field production system and under different irrigation depth. Irrigation treatments consisted in 0.25, 0.50, 0.75 and 1.0 (rate of crop evapotranspiration) and the control (no-irrigation). Two trials were conducted in the 2013-2014 and 2014-2015 season from September to March. The determination of the costs of crop production was based on the methodology of the total cost and gross operating revenues calculated based at the producer level. The lowest yield was obtained with the open field treatment and the highest with irrigation rate of 0.75 of evapotranspiration, with internal rate of return of 0.29 and 0.84 respectively. The net profit for rainfed agriculture for a simulated 10 years of study, projections oscillate between R$ 6,000-13,000, and with irrigation rate of 0.75 between R$ 38,000-48,000. The investment of the irrigation system is justified, as a supplementary tool for production, necessary for profitability in the crop. The cultivation is economically profitable and has a fast return of investment.